Africa’s low COVID-19 mortality rate: A paradox? (2020)
BACKGROUND As COVID-19 continues to spread worldwide with high number of fatalities first in China, then even higher fatalities in Italy, Spain, United Kingdom, United States, and other advanced countries; most African countries with less advanced healthcare systems ironically, continue to experience lower COVID19 mortality rates. This is even as the pandemic has reached its peak, plateaued or sliding downwards. It is presently slowly rising again in some countries though not as rapidly as before. This study is therefore, aimed at determining the predictors of COVID-19 mortality rate. This may help explain why Africa’s COVID-19 mortality rate is ironically lower than that of more advanced countries with better health systems. This will also assist various governments balance COVID-19 restrictive and socioeconomic measures. METHODOLOGY This is an analytic review that used pre-COVID era population data and current COVID-19 mortality figures to determine predictors of COVID-19 mortality rates. Pearson’s correlation was used to test the association between some population variables, and COVID-19 mortality rates. Then, stepwise multiple regression analysis was used to determine significant predictors of COVID-19 mortality rates. RESULTS Significant positive predictors of COVID-19 mortality rate included pre-COVID era ‘65yr+ mortality%’ (R square=0.574, B=2.86, p<0.001), population mean age (R square=0.570, B=4.77, p=0.001), and life expectancy (R square=0.524, B=1.67, p=0.008). Pre-COVID era CVD deaths was a negative predictor of COVID-19 mortality rate (R square=0.524, B=-0.584, p=0.012). CONCLUSION Africa’s COVID-19 lower mortality rate is due to the lower population mean age, lower life expectancy, lower pre-COVID era ‘65yr+ mortality rate’, and lower pool of persons surviving and living with cardiovascular diseases.